Clinical events in a large prospective cohort of children with sickle cell disease in Nagpur, India: evidence against a milder clinical phenotype in India. Issue 10 (9th June 2016) - Jain, Dipty; Arjunan, Aishwarya; Sarathi, Vijaya; Jain, Harshwardhan; Bhandarwar, Amol; Vuga, Marike; Krishnamurti, Lakshmanan
Abstract: Background: The clinical phenotype of sickle cell disease (SCD) has been reported to be milder in India than in the United States. The objective of this large single‐center study was to examine the rate of complications to define the phenotype of SCD in India. Methods: The rate of complications per 100 person‐years in 833 pediatric SCD patients for 1954 person‐years in Nagpur, India including those diagnosed on newborn screen (NBS) and those presenting later in childhood (non‐NBS) was compared to those reported in the cooperative study of sickle cell disease (CSSCD). Event rates were also compared between patients belonging to scheduled castes (SCs), scheduled tribes (STs), and other backward classes (OBC). Results: Comparison of CSSCD versus Nagpur NBS versus Nagpur non‐NBS for rates of pain (32.4 vs. 85.2 vs. 62.4), severe anemia (7.1 vs. 27 vs. 6.6), stroke (0.7 vs. 0.8 vs. 1.4), splenic sequestration (3.4 vs. 6.7 vs. 1.6), acute chest syndrome (24.5 vs. 23.6 vs. 1.0), and meningitis (0.8 vs. 0 vs. 0.1) revealed more frequent complications in Nagpur compared to CSSCD. Comparison of ST, SC, and OBC for rates of pain (84.6 vs. 71.9 vs. 63.5), acute chest syndrome (3.6 vs. 2.8 vs. 2.2), severe anemia (5.4 vs. 9.5 vs. 11.4), stroke (1.2 vs. 0.4 vs. 0.3), splenic sequestration (0.6 vs. 2.4 vs. 1.9), and meningitis (0.8 vs. 0 vs. 0.1) revealed significantly more frequent complications among ST. Conclusions: SCD‐related complications are more frequent in Indian children than that observed in CSSCD. Further study is indicated to define SCD phenotype in India.